Sosialisasi Penguatan Peran Pemilih Pemula menuju Pilkada Yang Berdemokrasi - Supriyanto; Andhi Nur Rahmadi; Imam Sucahyo; Verto Septiandika; Reny Candra Dewi; Mastina Maksin (CV. ITTC INDONESIA, 2024)
The existence of the state is inseparable from political activities. All parties have a role in state politics. Including the younger generation who have a role in politics, such as becoming first-time voters in central and regional elections. The role of novice voters who actively participate in elections shows the success of democracy in a country. However, the findings in the field are still many who do not understand about politics and the role of novice voters. This finding moved the service team to organize socialization to the younger generation. Service activities are carried out with a participatory action research (PAR) model. Service partners are aimed at students of the Faculty of Social and Political Sciences, Panca Marga University in the second and fourth semesters. The service activity with the theme